2020
DOI: 10.1155/2020/7361492
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Foveal Avascular Zone Area in Healthy Eyes among Young Chinese Adults

Abstract: Purpose. To evaluate the influence of systemic and ocular factors on the foveal avascular zone (FAZ) area in young Chinese subjects’ healthy eyes. Methods. The current observational, cross-sectional study included 344 eyes from 172 healthy individuals (103 women, 69 men). Optical coherence tomography angiography realized with the split-spectrum amplitude-decorrelation angiography (SSADA) algorithm was used to assess the area of superficial FAZ. To determine the related factors and to reveal their potential cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 36 publications
7
26
0
Order By: Relevance
“… 20 found no significant association between FAZ area and axial length in a multivariate analysis. Zhou and colleagues 12 also reported no significant association between FAZ area and axial length; they suggested that the lack of association may have been related to differences in experimental designs, compared with previous studies. Additionally, the specific range of axial length among enrolled volunteers might influence the association with FAZ area.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“… 20 found no significant association between FAZ area and axial length in a multivariate analysis. Zhou and colleagues 12 also reported no significant association between FAZ area and axial length; they suggested that the lack of association may have been related to differences in experimental designs, compared with previous studies. Additionally, the specific range of axial length among enrolled volunteers might influence the association with FAZ area.…”
Section: Discussionmentioning
confidence: 89%
“…To the best of our knowledge, few studies have focused on these influencing factors. 11 , 12 In this study, we used OCTA to measure the FAZ and identify potential influencing factors from among ocular and systemic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Our study is in line with the OCT angiography studies as macular microvasculature changes, including in FAZ areas, are known to be correlated with macular RNFL thickness. 37 However, it is still unknown whether enlargement of the FAZ precedes macular RNFL thinning, which is the main mechanism of the association between cognitive decline and macular retinal changes in the microvasculature and neural structures.…”
Section: Discussionmentioning
confidence: 99%
“… 26 28 Myopes had lower superficial and deep vessel/perfusion density and higher vascular resistance index than emmetropes in a number of previous studies. 19 , 20 , 22 , 26 36 However, the role of these factors in diurnal variation of OCT-A indexes over 24 hours is not known.…”
mentioning
confidence: 99%